EYE MOVEMENT BEHAVIOUR IN READING: DOES TEXT SIZE MATTER? - Buari, Noor Halilah Buari (International Journal of Allied Health Sciences, 2021)
Reading efficiency is not only of the main concerns among the teachers, publishers, but also eye care practitioners. It gives indirect information on the visual capability to recognise letters and words, undergoes complex cognitive processing and synthesis into speech reading. The size of the text was among factors that might affect the quality of reading. In the investigation of the effect of text legibility, the eye movement behaviour in terms of saccades and fixation were recorded, tracked and analysed. Significant changes in eye movements behaviour in terms of saccades and fixations occurred not only among young readers but also in older readers. The eye movements behaviour showed an adaption to the changes in shape, and size of presented reading materials for better understanding of reading.